Depression in patients of primary knee osteoarthritis: A cross-sectional study - Pooja Dhaon; Haseeb Khan; Rana Ravneesh Singh; Mukesh Shukla (Indian Journal of Rheumatology)
Aim and Objective: The aim and objective are to find the prevalence of depression and its relationship with functional status in patients with primary knee osteoarthritis (OA). Materials and Methods: The present study included 100 patients (33 males and 67 females) of primary knee OA fulfilling the American College of Rheumatology criteria. Demographic and diseases variables were recorded for all patients. Functional status was assessed using the Western Ontario and McMaster Universities Index (WOMAC), and depression was assessed using the Hamilton Depression Rating Scale (HAM-D). Results: Significant depression (HAM-D >13) was present in 19% of patients. Depression was associated with female sex and associated comorbid conditions. There was a significant positive correlation between WOMAC score and HAM-D score in all patients. Conclusion: Female patients with knee OA have associated depression, which is associated with poor functional status.